Sea of grass : the conquest, ruin, and redemption of nature on the American prairie - Hage, Dave; Marcotty, Josephine (Random House, 2025)
"The North American prairie is an ecological marvel. One cubic yard of prairie sod contains so many organisms that it rivals the tropical rainforest for biological diversity. And like the rainforest, it showcases nature's prodigious talent for symbiosis. The lush carpet of grasses feeds a huge population of grazing animals and is home to some of the nation's most iconic creatures--bison, elk, wolves, pronghorn, prairie dogs, and bald eagles. These creatures return the favor by spreading nitrogen and seeds across the prairie in their manure, and the grazers in turn feed prairie predators, and when they die, they return their store of organic matter to the living soil. When European settlers encountered the prairie nearly 200 years ago, rather than recognizing a natural wonder they saw a daunting landscape of root-tangled soil. But with the development of the steel plow, artificial drainage, and nitrogen fertilizers, in mere decades they converted the prairie into some of the richest farmland on Earth--a transformation unprecedented in human history. American farmers fed the industrial revolution and made North America a breadbasket for the world, but their progress came at a terrible cost: the forced dislocation of indigenous peoples, pollution of the continent's rivers, and the catastrophic loss of wildlife. Today, as these trends build toward an environmental crisis, industrial agriculture has resumed its assault on the prairie, plowing up the remaining grasslands at the rate of one million acres a year. Farmers have an opportunity to protect this extraordinary landscape, but trying new ideas can mean ruin in a business with razor-thin margins and will require help from Washington, D.C., and from consumers who care about the land that feeds them. Veteran journalists and Midwesterners Dave Hage and Josephine Marcotty follow the history of humanity's relationship with this incredible land, offering a deep, compassionate analysis of the difficult decisions as well as opportunities facing agricultural and Indigenous communities. Sea of Grass is a vivid portrait of one of the world's most miraculous and significant ecosystems, making clear why the future of this region is of essential concern far beyond the heartland"--